PENGEMBANGAN BAHAN AJAR MENULIS TEKS PROSEDUR DENGAN MODEL PROJECT BASED LEARNING BERBASIS MEDIA AUDIO VISUAL (VIDEO) PADA SISWA SMP IT HUDA WAN NUR LANGSA - Nuriana, Nuri (Universitas Islam Sumatera Utara, 2024)
This research focuses on developing teaching materials for writing procedural texts based on project based learning with audio visual (video) media for SMP IT Huda Wan Nur Langsa. The Borg and Gall research and development method was used in this research. This research involves ten steps, starting from preliminary research to creating the final product. The research results include prototypes of teaching materials that have been created, which are then tested for validity and practicality. The research results show that (1) the results of the Material Expert Assessment of the Appropriateness of the Content of Teaching Materials with an average value of (3.4) are in the good category; (2) The feasibility aspect of teaching materials with an average value of (3.38) is in the good category; (3) The Material Expert Component aspect regarding Feasibility of Presentation with an average value of (3.36) is in the good category; and (4) Design Expert Assessment Component (3.4) in the good category. Referring to the validation that has been carried out, procedural text teaching materials using the PLBL model based on Audio Visual Media are feasible to be developed and implemented in learning in schools.